Pathological changes in the osteoarticular system during COVID-19 drug therapy (review of literature) - A. N. Tsed; N. E. Mushtin; A. K. Dulaev; A. V. Shmelev (Вестник хирургии имени И.И. Грекова)
The recommended drugs for the treatment of COVID-19 are, on the one hand, experimental in nature, but at the same time, they have many side effects that cause long-term complications in organs and systems, including osteoarticular. Based on the analysis of modern domestic and foreign literature, to determine the effect of not only the new coronavirus infection COVID-19, but also the drugs used to treat it, on the human osteoarticular system. In the course of the study, a scientific search was made for publications in the electronic databases PubMed, MedLine and e-Library for the period from January 2000 to October 2021 for the main keywords. Due to successive “waves” of the COVID-19 pandemic, the number of patients receiving non-specific therapy, including corticosteroids, will increase in the coming years. Preliminary data on COVID-19 and similar trends during the Sars-COV-1 epidemic of 2003 show that the pathogenesis of Sars- Cov-2 and its treatment with high doses of corticosteroids may increase the risk of osteonercosis in patients, which will inevitably lead to an increase in orthopedic diseases in patients not only the middle age group, but also young patients in the near future. Currently, studies are required aimed at risk stratification, studying the pathogenesis of damage to the musculoskeletal system after COVID-19 and the effectiveness of preventive and therapeutic measures in such patients.